Analysis of infrared emissivity of EB-PVD thermal barrier coatings at the microscopic level - Ying Cui; Yuhui Liu; Shan Gao; Liwei Chen; Jing Jiang; Yi Niu; Chao Wang (Case Studies in Thermal Engineering, 2024)
Thermal barrier coatings (TBCs) applications of yttria-stabilized (YSZ) are widely utilized on turbine blades of aviation engines due to its low thermal conductivity and high electrical conductivity. Predicting the infrared emissivity aids in monitoring blade operating temperatures, ensuring safe engine operation. This paper innovatively introduces a novel three-dimensional columnar EB-PVD coating model and utilizes the FDTD method to predict emissivity. The model exhibits strong consistency with experimental results for predicted emissivity in the short-wave infrared band (1.4–3 μm). The unique microstructure of the EB-PVD thermal barrier coatings significantly influence the infrared emissivity. The results indicate that vertically uniform arranged feathers exhibit higher emissivity levels compared to feathers with varying densities. Additionally, increasing the thickness of the ceramic top coating and reducing spherical closed porosity also enhance the emissivity levels. This research provides guidance for controlling emissivity at the microscale in the preparation of thermal barrier coatings.